If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -5 * 5 = 7 Multiply -5 * 5 4y + -25 = 7 Reorder the terms: -25 + 4y = 7 Solving -25 + 4y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 4y = 7 + 25 Combine like terms: -25 + 25 = 0 0 + 4y = 7 + 25 4y = 7 + 25 Combine like terms: 7 + 25 = 32 4y = 32 Divide each side by '4'. y = 8 Simplifying y = 8
| 7=n/5-3 | | 8c+5=23-x | | -w/2=28 | | B-3=-23 | | (u-8)*10=80 | | -21=-v/6 | | 400-30y=150+20y | | 2x/3=3-5(2-x)/4 | | 2tanx=-x | | (q-4)*4=8 | | 50-5x=70-45x | | 6+4b= | | (tanx)/x=0.5 | | 2x-1.5=15 | | w/2=-57 | | (y-7)+2(4y+8)=81 | | 4.6g+9=1.6g+15 | | -15n+9n+6y-11n= | | x^2+6X-11=-4 | | 4y=y+1 | | 2/3x1/6= | | 45q^3-65q=45-65 | | 5x-20+x=50 | | (x+4)(x-7)=o | | 10y=5+45 | | 2x-7-5x^2+2= | | 4(3x)=4(2x-1) | | 2x+4=6*(2x-4) | | 55000+2500x=6200+2000x | | (X+9)(3x-9)=0 | | -10(5+5)=-84 | | 13(11)-28=90 |